Ageloline A, new antioxidant and antichlamydial quinolone from the marine sponge-derived bacterium Streptomyces sp. SBT345. Issue 25 (22nd June 2016) - Cheng, Cheng; Othman, Eman M.; Reimer, Anastasija; Grüne, Matthias; Kozjak-Pavlovic, Vera; Stopper, Helga; Hentschel, Ute; Abdelmohsen, Usama R.
Graphical abstract: Highlights: A new chlorinated quinolone was isolated from the sponge-associated Streptomyces sp. SBT345. Ageloline A showed antioxidant potential. Ageloline A inhibited the formation and growth of Chlamydia trachomatis . Abstract: A new chlorinated quinolone, ageloline A, was isolated from the broth culture of Streptomyces sp. SBT345 that was cultivated from the Mediterranean sponge Agelas oroides . The structure of this compound was determined by spectroscopic analysis including 1D and 2D NMR as well as HR-ESI-MS experiments. Ageloline A exhibited antioxidant potential using cell-free and cell-based assays and was further able to reduce oxidative stress and genomic damage induced by the oxidative stress inducer 4-nitroquinoline-1-oxide (NQO). Moreover, ageloline A inhibited the formation and growth of Chlamydia trachomatis inclusion in a dose-dependent manner with an IC50 value of 9.54 ± 0.36 μM. Interestingly, experimental data showed that the antichlamydial activity of ageloline A might be related to its antioxidant potential. These results demonstrate that sponge-associated actinomycetes are rich sources for natural products with new pharmacological activities and relevance to drug discovery.